Strength and conditioning for volleyball: a review - Rebelo, A.; Valente-dos-Santos, J.; Pires, I. G.; Arrais, I.; Pereira, J. R.; Turner, A. N. (Strength and Conditioning Journal, 2025)
Volleyball, with its global popularity and rigorous competition schedules, presents unique challenges in athlete conditioning and injury risk reduction. This narrative review synthesizes the current understanding of the physical demands and injury risks associated with elite volleyball play, offering a detailed analysis of match play dynamics and prevalent injury mechanisms. It emphasizes the important role of strength and conditioning (S&C) coaches in developing training programs to enhance performance and mitigate injury risks through strategic exercise selection and periodization. The review provides a thorough needs analysis, highlighting specific conditioning requirements for different player positions and detailing effective physical testing protocols. Recommendations are made for implementing structured S&C programs, which are vital for preparing athletes for the physical challenges of competitive volleyball. Practical guidelines are outlined for S&C coaches to optimize training outcomes, including suggestions for drill sequences and conditioning routines that reflect the sport-specific demands of volleyball. Thus, this review aims to equip coaches, trainers, and athletes with the knowledge and tools necessary to elevate their performance and safeguard against injuries, thereby contributing to the advancement and sustainability of volleyball as a high-intensity competitive sport.